THE ISSUES OF EXPRESSING MERONYMS IN DICTIONARIES (COMPARED IN EXAMPLES IN ENGLISH AND UZBEK LANGUAGES) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This research is about meronyms which is based on how to express the meronyms in dictionaries analyzing the expressions of part-whole relationships within lexicographical sources. Meronyms, as a fundamental type of semantic relation, describe how a term denotes a part of a larger whole (e.g., “root” is a meronym of “tree”). This study examines how different dictionaries define, classify, and structure meronyms, considering linguistic, cognitive, and lexicographical perspectives. Key issues include consistency in defining meronyms, variations across different languages and dictionary types, and the role of meronyms in semantic systems. It also addresses challenges in computational lexicography, where meronymic relationships are crucial for natural language processing (NLP) usage. By analyzing existing dictionary models and proposing improvements, this research contributes to the development of more comprehensive and systematic lexicographical resources.